Bone Mesenchymal Stem Cell-Derived Small Extracellular Vesicles Ameliorated Lipopolysaccharide-Induced Lung Injury Via the miR-21-5p/PCSK6 Pathway - Bo Cai; Weidong Song; Song Chen; Jie Sun; Rui Zhou; Zhen Han; Jian Wan (Journal of Immunology Research)
Acute lung injury (ALI) is a life-threatening disease that currently lacks a cure. Although stem cell-derived small extracellular vesicles (sEVs) have shown promising effects in the treatment of ALI, their underlying mechanisms and responsible components have yet to be identified. Proprotein convertase subtilisin/kexin type 6 (PCSK6) is a gene involved in inflammation and a potential target of miR-21-5p, a microRNA enriched in stem cell-derived sEVs. The current study investigated the role of PCSK6 in lipopolysaccharide (LPS)-induced ALI and its interaction with miR-21-5p. Notably, our results showed that PCSK6 expression was positively correlated with LPS stimulation. Knockdown of PCSK6 ameliorated LPS-induced inhibition of proliferation and upregulation of permeability in human BEAS-2B cells, whereas PCSK6 overexpression displayed the opposite effects. BEAS-2B cells were able to actively internalize the cocultured bone mesenchymal stem cell (MSC)-derived sEVs (BMSC-sEVs), which alleviated the cell damage caused by LPS. Overexpressing PCSK6, however, eliminated the therapeutic effects of BMSC-sEV coculture. Mechanistically, BMSC-sEVs inhibited PCSK6 expression via the delivery of miR-21-5p, which is directly bound to the PCSK6 gene. Our work provides evidence for the role of PCSK6 in LPS-induced ALI and identified miR-21-5p as a component of BMSC-derived sEVs that suppressed PCSK6 expression and ameliorated LPS-induced cell damage. These results reveal a novel molecular mechanism for ALI pathogenesis and highlight the therapeutic potential of using sEVs released by stem cells to deliver miR-21-5p for ALI treatment.